Diagnostics of the physical conditions in the powerful flare on October 28.2003 - Stodilka, M.I.; Lozitsky, V.G. (Известия Крымской астрофизической обсерватории, 2007)
To study physical conditions in the solar flare we chose temperature sensitive lines of neutral iron with Lande-factor being equal to zero λ5434.534A, λ5123.73A. Usually such lines do not allow one to reproduce magnetic fields. Upper levels of FeI are connected with strong UV-lines which are thick in the photosphere and temperature minimum region and the lines support the level excitation nearly thermal. So non-LTE parameters of the lower and upper levels for the lines considered here are approximately equal that leads to S ≈ B; the latter condition provides the high sensitivity of lines to the temperature stratification.